Association between birthweight discordance and extrauterine growth restriction among preterm twins: a national multi-center study in China - Chen, Qian; Shi, Bijun; Lin, Lizi; Lu, Danfang; Zhang, Jiayi; Ren, Shuhua; Huang, Kang; Shen, Wei; Chen, Zhifeng; Liu, Jin; You, Chunming; Li, Guifang; et al. (Frontiers in Pediatrics, 2026)
BackgroundThis multicenter study investigated the association between birthweight discordance (BWD) and extrauterine growth restriction (EUGR) in preterm twins, and evaluated the modifying role of small for gestational age (SGA).MethodsData from 2,496 infants (1,248 twin pairs) admitted to 22 Chinese NICUs (2018–2020) were analyzed. BWD was calculated as the percentage difference in birthweight between larger and smaller twins, categorized into four groups (≤15%, 15%–20%, 20%–25%, >25%). EUGR was defined as discharge weight below the 10th percentile for corrected gestational age and sex (Fenton's chart). A generalized linear mixed model was employed to analyze the association between BWD and EUGR. Modification analysis was performed to assess the effect of SGA on this association.ResultsBWD of >25% was associated with a significantly increased risk of EUGR compared to BWD ≤15% (adjusted OR = 1.59, 95% CI: 1.05–2.41). Stratified analysis revealed a consistent association in SGA infants (OR = 1.38, 95% CI: 1.30–1.47).ConclusionFindings highlight BWD as a critical risk factor for EUGR, particularly in SGA twins. This association suggests that future research should investigate whether tailored monitoring and nutritional interventions in NICUs could help mitigate these growth disparities.